Classes to Passes: Is Class Attendance a Determinant of Grades in Undergraduate Engineering Subjects? - Anderson, T; Whittington, C; Li, X (Southern Cross University, 2016)
CONTEXT The rapid advancement in information technologies in recent times has opened a number of opportunities to the higher education sector. This has led to a revision of the traditional educational paradigm through the advent of “online/flexible content delivery” and “massive open online courses (MOOCs)”. However, despite these advances, there is an underlying question as to the role of face-to-face teaching in the modern era. In this respect a number of studies have demonstrated that attendance at lectures and tutorials could be strongly correlated to students’ success in their studies. PURPOSE This work aims to determine if the observations relating to student attendance apply to students studying engineering at undergraduate level and to determine the implications of this for teaching practice in engineering. APPROACH For this study an attendance register was kept for several courses across a semester for students enrolled in papers spanning a range of years and disciplines. Subsequently, the relationship between each student’s attendance and his/her final grade was examined. RESULTS The results showed that for two of the three courses examined in this study there was a strong relationship between attendance and final grade. However, in the third course, this relationship was less clear and rather there was a stronger correlation with the students’ performance in a pre-requisite course. CONCLUSIONS In summary, it can be said that attendance can serve as an indicator for a student’s grade, however, other factors can also impact this. In this respect the work illustrates not only the benefits of student attendance but also the flow through impact of knowledge gained in pre-requisite courses.
Keywords: Attendance; Grades; Pre-requisites